(untitled) (Malay Literature, 2017)
This article discusses the contribution of Dato’ Ahmad Kamal Abdullah or Kemala regarding the development of Malay poetry in Malaysia and the history of Malay poetry in the archipelago. This article is based fully on the essays compiled in Landskap Ungu (2010). It examines Kemala’s contribution to the Malay art of poetry composition, the approach or the evaluation used in analyzing Malay poetry, specifically in interpreting Islamic poetry and the country’s sociopoliticsal landscape, as well as comparing the quality of the art of poetry of international poets with that of some of Malaysia’s poets. Apart from that, other issues are also discussed, such as the art concept of sufi poetry which is the basic expression of some Malay poets, either in Indonesia or Malaysia. Kemala’s contribution is exceptional and has proven to be very significant in the development of Malay poetry with regard to his capability as a critic and a disciplined researcher, especially in the world of Malay poetry. His level of thought and intellectualism boost the quality of the art of expression of creative thinking locally or universally. Keywords: epistemology, aesthetics, hermeneutics, irony, critiques, literature, mystique, thinker, sufi, sufi poetry, semiotic, symbolism, theory of literature